Properties of concrete containing coal bottom ash as hydraulic binder substitution - Khairunisa, Muthusamy; Wong, Wang Hui; Nabilla, Mohamad; Rajan, Jose; Budiea, Ahmed Mokhtar Albshir; Abdul Majeed, Anwar P. P.; Kırgız, Mehmet Serkan (Elsevier Ltd, 2023)
The growing concrete production that directly increases demand for cement also pushes for rising harvesting of limestone from the hills, thus destroying the natural landscape and wildlife habitat. The increasing disposal of coal bottom ash (CBA) generated by coal power plants and greenhouse gas emission by cement industry causes degradation of environment. The approach of integrating CBA as partial cement replacement in concrete would reduce waste released to the environment from the industries. The present research investigates the effect of ground CBA as a mixing ingredient toward workability, compressive strength, and splitting tensile strength of water-cured concrete. Various concrete mixes were produced by varying percentages of CBA ranging from 0% to 50% as partial cement replacement. The concrete experience rises in workability and strength declination as the content of CBA used as partial cement replacement grows.